Grain-finish artificial leather and its manufacturing method
By using high-density and low-density non-woven layers and water-based polyesterene in the silver-side simulated leather and adjusting its porosity, the problems of insufficient wrinkles and surface adsorption of the existing silver-side simulated leather are solved, and the effects of fine wrinkles and high smoothness are achieved.
Patent Information
- Application Number
- JP2021016298
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-04
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2041-02-04
AI Technical Summary
The wrinkles generated by existing silver-surface emulated leather materials are not dense enough when bending, and surface adsorption is prone to occur during the insole forming process, affecting the surface smoothness.
A simulated leather substrate containing the first and second non-woven layers is adopted, the first non-woven layer consists of high-density fibers, the second non-woven layer has a low fiber density, and 5-18% water-based polyesterene is applied between the fibers, and the silver-faced resin layer is only covered on the first non-woven layer, and the density and flexibility of the surface layer are ensured by adjusting the porosity A and porosity B of the first and second non-woven layers.
The fine wrinkles generated by the silver-surface simulated leather material when bending are realized, the surface adsorption phenomenon is avoided, the soft touch is maintained, and the surface smoothness during the molding process is improved.
Smart Images

Figure 0007671150000002 
Figure 0007671150000003 
Figure 0007671150000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a grain-finished artificial leather having a grain surface resin layer applied to an artificial leather substrate containing a nonwoven fabric. [Background technology]
[0002] Conventionally, grain-finished artificial leathers have been known in which a grain-finished resin layer such as a polyurethane resin layer is laminated on the surface of an artificial leather substrate in which polyurethane is applied to the internal voids of a nonwoven fabric. Such grain-finished artificial leathers are widely used as materials for bags, upper materials for shoes, clothing, etc.
[0003] Natural leather has a high specific gravity and a high solidity, so when it is bent, fine wrinkles are generated. On the other hand, grain-finished artificial leather has a lower solidity than natural leather, so when it is bent, large, rough wrinkles are generated. Such a difference in the state of wrinkles when it is bent is recognized as a major difference between grain-finished artificial leather and natural leather. For this reason, there is a demand for improvement in grain-finished artificial leather so that it can generate fine wrinkles in order to bring the texture closer to that of natural leather.
[0004] Furthermore, grain-finished artificial leather is widely used as a shoe upper material. The upper part of a shoe using grain-finished artificial leather as the upper material is manufactured through the following process. Pieces of grain-finished artificial leather cut along a pattern are sewn, and then the grain-finished artificial leather pieces are pulled tightly against a shoe last under tension, and the shape of the upper part of the shoe is set by applying heat to set it. This type of molding is also called tsuri-komi.
[0005] In the process of pulling the grain-finished artificial leather into a shoe mold while pulling it, the grain-finished artificial leather may become thin and show an appearance called "surface mottling," in which the uneven shape of the fibers that form the artificial leather base material appears on the surface of the grain-finished resin layer. This type of surface mottling is not seen in natural leather, and is recognized as a defect in leather shoes, where a smooth appearance is preferred.
[0006] For the purpose of improving the appearance and feel of grain-finished artificial leather, for example, the following techniques are known.
[0007] For example, the following Patent Document 1 discloses a grain-finished artificial leather that is preferably used for shoes and has a soft, full-feeling texture similar to that of natural leather and high peel strength. Specifically, the patent document discloses a grain-finished artificial leather that is made of an entangled nonwoven fabric mainly made of ultrafine fibers and an elastic polymer impregnated therein, and that is obtained by forming a grain-surface resin layer on an artificial leather substrate that satisfies the following requirements: (1) the average single fineness of the ultrafine fibers is 0.06 dtex or less, (2) the strength of the ultrafine fibers is less than 4.0 cN / dtex, (3) the apparent density A of the elastic polymer constituting the front side of the artificial leather substrate and the apparent density B of the elastic polymer constituting the back side satisfy 0.07+B≧A≧0.01+B, (4) the mass ratio of the entangled nonwoven fabric to the elastic polymer is 40:60 to 70:30, and (5) the apparent density of the artificial leather substrate is 0.30 to 0.50 g / cm. 3 To be.
[0008] Also, the following Patent Document 2 discloses a grain-finished artificial leather that is excellent in mechanical properties, particularly in peel strength between the artificial leather substrate and the grain layer, has a soft feel, and has both natural leather-like creases and a full feel. Specifically, the invention discloses a grain-finished artificial leather that has a grain layer on at least one side of an artificial leather substrate made of a long-fiber entanglement body made of ultrafine long fibers with an average fineness of 0.001 to 0.5 dtex and a polymeric elastomer optionally impregnated with the entanglement body, and that is bonded to the artificial leather substrate by an adhesive layer, and that simultaneously satisfies the following conditions (1) and (2): (1) the mass ratio of polymer elastomer / ultrafine long fiber in the artificial leather substrate is in the range of 0 / 100 to 10 / 90, (2) A1 / A2≧0.85 (wherein A1 is the average spatial occupancy of the ultrafine long fiber in any cross section parallel to the thickness direction of the grain-finished artificial leather, excluding the polymer elastomer in a thickness range of 0 to 100 μm from the boundary between the adhesive layer and the artificial leather substrate toward the artificial leather substrate, and A2 is the average spatial occupancy of the ultrafine long fiber in any cross section parallel to the thickness direction of the grain-finished artificial leather, excluding the polymer elastomer in a thickness range of 100 to 300 μm from the boundary between the adhesive layer and the substrate layer toward the substrate layer).
[0009] Furthermore, the following Patent Document 3 discloses a sheet-like material that is soft, has a solid feel, is excellent in the feeling of folding and wrinkling when made into a grain-finished sheet-like material, and has a natural leather-like texture with a sense of unity without the feeling of tension on one side as described above. Specifically, the patent document discloses a leather-like sheet-like material that is made of a three-dimensionally entangled nonwoven fabric and a polyurethane binder solidified into a microporous state, and that is characterized in that both the fiber and the polyurethane binder have an apparent density gradient in the same direction in the thickness direction of the sheet-like material by incorporating the polyurethane binder in multiple layers in the nonwoven fabric that has an apparent density gradient in the thickness direction. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2005-097763 A [Patent Document 2] JP 2012-17541 A [Patent Document 3] Japanese Patent Application Publication No. 6-280145 Summary of the Invention [Problem to be solved by the invention]
[0011] As mentioned above, techniques have been proposed to achieve a texture similar to that of natural leather and to achieve both a solid feel and a supple texture. However, it has been difficult to obtain a grain-finished artificial leather that can achieve dense surface creases without impairing the supple texture and can also suppress the occurrence of surface blemishes during the stitching process.
[0012] The present invention aims to provide a grain-finished artificial leather which has solved the above problems, maintains a supple texture, has fine surface creases, and suppresses the occurrence of surface blemishes during stitching. [Means for solving the problem]
[0013] One aspect of the present invention is an artificial leather substrate comprising a fiber-entangled structure including a first nonwoven fabric layer mainly made of a first fiber and a second nonwoven fabric layer mainly made of a second fiber, and 5 to 18% by mass of a water-based polyurethane provided in voids in the fiber-entangled structure, and a grain surface resin layer applied to the surface of the first nonwoven fabric layer, wherein the average fineness of the first fiber is is 0.075~ 0.40dte x The average fiber length of the second fiber is Degree is 0.05~0 .60dte x can be The average fineness of the second fibers is 1.5 times or more the average fineness of the first fibers,The first nonwoven fabric layer has a higher fiber density than the second nonwoven fabric layer, and in a cross section in the thickness direction of the artificial leather substrate, in a first region which is a 200 μm-thick region from the interface between the grain surface resin layer and the first nonwoven fabric layer toward the second nonwoven fabric layer, and in a second region which is a region excluding the first region, the porosity A of the first region is 10 to 20%, and the porosity B of the second region is 2 to 3.3 times the porosity A. Here, "mainly" means that 60% by mass or more of the fibers forming the first nonwoven fabric layer are the first fibers, or 60% by mass or more of the fibers forming the second nonwoven fabric layer are the second fibers.
[0014] In such a grain-finished artificial leather, the fiber density of the first nonwoven fabric layer is made higher than that of the second nonwoven fabric layer, the porosity A of the first region near the surface layer of the first nonwoven fabric to which the grain surface resin layer of the artificial leather substrate is attached is made low, such as 10 to 20%, and the porosity B of the second region of the lower layer is adjusted to be significantly higher, such as 2 to 3.3 times the porosity A. As a result, only the surface layer of the first nonwoven fabric layer attached to the grain surface resin layer is made more solid, and fine creases can be easily generated on the surface of the grain surface resin layer when it is folded. In addition, the content of the water-based polyurethane is low, such as 5 to 18 mass%, and the porosity B of the second region is 2 to 3.3 times the porosity A of the first region, so that the middle to lower layers of the artificial leather substrate can maintain a supple texture. In addition, the water-based polyurethane does not excessively constrain the first fiber and the second fiber. With this configuration, the porosity A of the first region is 10 to 20%, which is significantly lower than the porosity B of the second region. Therefore, when the grain-finish artificial leather is used as an upper material to manufacture shoes, even when it is fitted into a shoe mold, the high porosity B of the second region makes it easy to relax the tension when bending, and because the first region is dense, it is less likely to cause surface irregularities in which the uneven shape of the fibers is exposed on the surface of the grain surface resin layer.
[0015] And the third The average fineness of the second fiber is 1.5 times or more the average fineness of the first fiber. Therefore,The porosity A of the first region as described above is set low, such as 10 to 20%, and the porosity B of the lower second region is easily adjusted to be 2 to 3.3 times the porosity A. It becomes easier.
[0016] Moreover, it is preferable that the porosity B of the second region is 15 to 40% higher than the porosity A of the first region, since this sufficiently provides the effect of preventing surface defects from occurring.
[0017] Furthermore, it is preferable that the fiber density of the first nonwoven fabric layer is 1.1 to 2.5 times that of the second nonwoven fabric layer, because the difference in void ratio as described above can be formed by the difference in fiber densities, thereby increasing the solidity of only the surface layer of the first nonwoven fabric layer that is attached to the silver surface resin layer, making it easier for fine creases to occur on the surface of the silver surface resin layer when folded.
[0018] It is also preferred that the first fiber is a long fiber and the second fiber is a short fiber. In such a case, the fiber density in the first region is likely to be denser, which makes it easier to generate fine wrinkles. In addition, the fiber density in the second region is likely to be sparser, which makes it easier to relax the tension when folded and absorb distortion, so that the effect of preventing surface irregularities is easily obtained.
[0019] It is more preferable that the ratio of the first nonwoven fabric layer to the total thickness of the first and second nonwoven fabric layers is 30 to 60%, since this makes it easier to adjust the void ratio as described above.
[0020] The artificial leather substrate has a density of 0.50 to 0.70 g / cm 3 It is preferable that the apparent density of the powder is 100% or more from the viewpoint of excellent solidity.
[0021] Furthermore, it is more preferable that the first and second fibers are polyester fibers, since these fibers have high heat shrinkability and therefore can be easily adjusted to the above-mentioned void ratio.
[0022] Another aspect of the present invention is a method for producing any of the above-mentioned grain-finished artificial leathers, comprising the steps of: preparing a first fiber web which is a web of a first islands-in-sea type composite fiber for forming a first fiber; and preparing a second fiber web which is a web of a second islands-in-sea type composite fiber for forming a second fiber; laminating at least one layer of a second fiber web on at least one surface of at least one layer of the first fiber web to form a laminated web; forming an entangled fiber sheet by entangling the first islands-in-sea type composite fiber and the second islands-in-sea type composite fiber which form the laminated web; and heat-shrinking the entangled fiber sheet to form a heat-shrinkable fiber sheet. a step of forming a fiber-entangled body including a first nonwoven fabric layer and a second nonwoven fabric layer by impregnating voids in the heat-shrinkable fiber sheet with an aqueous liquid of water-based polyurethane and heating and drying the sheet to provide the water-based polyurethane, a step of forming an artificial leather substrate by flattening the surface of the first nonwoven fabric layer, and a step of coating the flattened surface of the first nonwoven fabric layer with a grain surface resin layer, wherein the island component ratio of the first islands-in-sea type composite fiber is higher than the island component ratio of the second islands-in-sea type composite fiber. This production method provides a grain-finished artificial leather that is resistant to fine creases and surface defects. Effect of the Invention
[0023] According to the present invention, there is obtained a grain-finished artificial leather which maintains a supple feel while reducing surface creases and which is capable of suppressing the occurrence of surface blemishes during stitching. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a scanning electron microscope (SEM) photograph of a cross section in the thickness direction of grain-finished artificial leather 10 obtained in Example 1, which is an example of the grain-finished artificial leather of the embodiment. [Diagram 2] FIG. 2 is a SEM photograph of a cross section in the thickness direction of the grain-finished artificial leather obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, a grain-finish artificial leather 10 according to one embodiment of the present invention will be described with reference to the drawings. Fig. 1 is a scanning electron microscope (SEM) photograph of a cross section of grain-finish artificial leather 10 in the thickness direction.
[0026] 1, the grain-finished artificial leather 10 comprises an artificial leather substrate 3 including a first nonwoven fabric layer 1 mainly made of a first fiber and a second nonwoven fabric layer 2 mainly made of a second fiber integrated and entangled with the first nonwoven fabric layer 1, and a grain surface resin layer 4 applied to the surface of the first nonwoven fabric layer 1. The first nonwoven fabric layer 1 has a higher fiber density than the second nonwoven fabric layer 2. The artificial leather substrate 3 contains 5 to 18 mass % of a water-based polyurethane 5 provided in voids in the fiber-entangled body including the first nonwoven fabric layer 1 and the second nonwoven fabric layer 2.
[0027] In a cross section in the thickness direction of such an artificial leather substrate 3, in a first region R1 which is a 200 μm thick region extending from the surface of the first nonwoven fabric 1 toward the second nonwoven fabric 2, and in a second region R2 which is the region excluding the first region R1, the porosity A of the first region R1 is 10 to 20%, and the porosity B of the second region R2 is 2 to 3.3 times the porosity A, resulting in a grain-finished artificial leather.
[0028] Such grain-finished artificial leather will be described in detail below along with an example of a manufacturing method thereof. The grain-finished artificial leather is manufactured, for example, through the following steps.
[0029] (1) preparing a first fiber web which is a web of a first islands-in-sea type composite fiber for forming a first fiber, and a second fiber web which is a web of a second islands-in-sea type composite fiber for forming a second fiber; (2) laminating at least one layer of a second fiber web on at least one surface of at least one layer of the first fiber web to form a laminated web; (3) forming an entangled fiber sheet by entangling the first islands-in-sea type composite fiber and the second islands-in-sea type composite fiber which form the laminated web; and (4) heat-shrinking the entangled fiber sheet to form a heat-shrinkable fiber sheet. (5) a step of impregnating voids in the heat-shrinkable fiber sheet with an aqueous liquid of water-based polyurethane and heating and drying to impart the water-based polyurethane; (6) a step of forming a fiber-entangled body including a first nonwoven fabric layer and a second nonwoven fabric layer by subjecting the heat-shrinkable fiber sheet to an ultrafine fiber treatment to which the water-based polyurethane has been imparted; (7) a step of flattening the surface of the first nonwoven fabric layer to form an artificial leather substrate; and (8) a step of coating the flattened surface of the first nonwoven fabric layer with a grain surface resin layer, thereby producing a grain-finished artificial leather.
[0030] In such a production method, the island component ratio of the first islands-in-sea type composite fibers is made higher than the island component ratio of the second islands-in-sea type composite fibers, and the average fineness of the second fibers is made higher than the average fineness of the first fibers, thereby making the fiber density of the first nonwoven fabric layer higher than the fiber density of the second nonwoven fabric layer.
[0031] In addition, in such a manufacturing method, the artificial leather substrate contains 5 to 18% by mass of water-based polyurethane, and is manufactured by adjusting the porosity A of the first region, which is a 200 μm-thick region extending from the interface between the grain surface resin layer and the first nonwoven fabric layer toward the second nonwoven fabric layer, and the porosity B of the second region, which is the region excluding the first region, to be 10 to 20%, and 2 to 3.3 times the porosity A. Each step will be described in detail below.
[0032] (1) preparing a first fiber web which is a web of a first islands-in-the-sea type composite fiber and a second fiber web which is a web of a second islands-in-the-sea type composite fiber; In producing an artificial leather substrate, a first fiber web containing first islands-in-sea type composite fibers for forming a first nonwoven fabric layer mainly made of a first fiber, and a second fiber web containing second islands-in-sea type composite fibers for forming a second nonwoven fabric layer mainly made of a second fiber are prepared.
[0033] The islands-in-sea type composite fiber is a fiber in which an island component resin, which forms a different type of domain from the sea component, is dispersed in a sea component resin, which forms a matrix, in the cross section of the fiber, and by removing the sea component, ultrafine fibers in the form of fiber bundles mainly composed of the island component resin are generated. The islands-in-sea type composite fiber can form fiber bundles of ultrafine fibers that retain voids inside, and therefore a flexible artificial leather base material can be obtained.
[0034] Examples of methods for producing a fiber web containing islands-in-sea type composite fibers include a method in which islands-in-sea type composite fibers are melt-spun using a spunbonding method, and the fibers are collected on a net without being cut to form a web of long fibers of continuous fibers, and a method in which islands-in-sea type composite fibers are melt-spun, drawn, and then further crimped as necessary, and the cut raw fiber is passed through a carding machine to form a web.
[0035] In the case of the spunbonding method, molten sea part resin and island part resin are separately discharged from individual nozzle holes of a melt composite spinning die, brought into contact with each other, and then deposited on a moving net in the form of a conveyor belt while being cooled by a high-speed air current, thereby forming a fiber web containing long islands-in-sea type composite fibers.
[0036] In the case of producing cut staple fibers, islands-in-sea type composite fibers are spun by a melt spinning method using a conjugate spinning die having a large number of nozzle holes arranged in a predetermined pattern, and then drawn. After further crimping is added as necessary, the cut raw cotton is passed through a carding machine to form a fiber web containing islands-in-sea type composite fibers of staple fibers.
[0037] The resulting fibrous web may also be heat pressed to impart dimensional stability.
[0038] Specific examples of the thermoplastic resin of the island components of the islands-in-sea type composite fiber include polyethylene terephthalate (PET), which is a copolymer of terephthalic acid units and ethylene glycol units, polybutylene terephthalate (PBT), which is a copolymer of terephthalic acid units and 1,4-butanediol units, polytrimethylene terephthalate (PTT), polyesters such as polyester elastomers, or modified polyesters such as modified products thereof; polyamide resins such as polyamide 6, polyamide 66, polyamide 610, aromatic polyamides, polyamide elastomers, or modified polyamides such as modified products thereof. The term "modified product" refers to a polymer in which a part of the main polymer forming units is replaced with a small amount of other monomer units for the purpose of adjusting the intrinsic viscosity, melting point, or crystallinity of the resin. For example, examples of small amounts of monomer units that modify polyester include asymmetric aromatic carboxylic acids such as isophthalic acid, phthalic acid, and 5-sodium sulfoisophthalic acid, aliphatic dicarboxylic acids such as adipic acid, and diols such as ethylene glycol, butanediol, neopentyl glycol, cyclohexanedimethanol, polyethylene glycol, and polypropylene glycol. By introducing these monomer units, the intrinsic viscosity, melting point, and crystallinity of each polyester can be adjusted. The thermoplastic resins may be used alone or in combination of two or more kinds. Among these, polyester is preferred because of its particularly high heat shrinkability.
[0039] On the other hand, specific examples of the thermoplastic resin of the sea component include polyvinyl alcohol-based resins, polyethylene, polypropylene, polystyrene, ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, styrene-ethylene copolymers, styrene-acrylic copolymers, etc. Among these, water-soluble polyvinyl alcohol-based resins, in particular ethylene-modified polyvinyl alcohol resins, are preferred because they tend to shrink when subjected to wet heat treatment or hot water treatment.
[0040] The thermoplastic resin of the island component and the thermoplastic resin of the sea component may each contain additives such as organic particles, inorganic particles, flame retardants, and antistatic agents, if necessary.
[0041] The mass ratio of the sea part to the island parts of the islands-in-sea type composite fiber is preferably in the range of sea part:island part=5:95 to 80:20. As described later, the first nonwoven fabric layer formed from the first fiber web is adjusted to have a higher fiber density than the second nonwoven fabric layer formed from the second fiber web. When the island part ratio of the first islands-in-sea type composite fiber is higher than the island part ratio of the second islands-in-sea type composite fiber, the fiber density of the first nonwoven fabric layer can be adjusted to be higher than the fiber density of the second nonwoven fabric layer. The lower the sea part ratio of the islands-in-sea type composite fiber, the more the fiber bundles of the ultrafine fibers formed are compressed, and therefore the higher the fiber density tends to be.
[0042] Specifically, the island component ratio of the first islands-in-sea type composite fiber is preferably 10 to 30% higher by mass than that of the second islands-in-sea type composite fiber.For example, it is preferable that the island component ratio of the first islands-in-sea type composite fiber is 60 to 80% by mass and that of the second islands-in-sea type composite fiber is 40 to 60% by mass, from the viewpoint of ease of adjusting the porosity as described above.
[0043] The number of island components in the islands-in-sea type composite fiber is, for example, preferably 5 to 200, more preferably 10 to 50, and particularly preferably 10 to 30. The greater the number of island components and the lower the fineness of the ultrafine fibers formed, the more the fiber bundles of the ultrafine fibers formed are compressed, and therefore the fiber density tends to increase.
[0044] The islands-in-sea composite fiber is melt spun to include island components that can be converted into ultrafine fibers having a predetermined average fineness by a subsequent ultrafine fiber forming treatment. Specifically, the average fineness of the first fiber is 0.40 dtex or less, and the average fineness of the second fiber is 0.60 dtex or less. The average fineness of the second fiber is preferably adjusted to be 1.5 times or more, and more preferably 1.6 to 10 times, the average fineness of the first fiber, from the viewpoint of easily forming a first nonwoven fabric layer having a higher fiber density than the second nonwoven fabric layer. In this way, by adjusting the average fineness and the content ratio of the first fiber and the second fiber, it becomes easy to adjust the void ratio as described above.
[0045] Average fineness of the first fibers formed from the first fibrous web is 0 It is preferably 0.075 to 0.40 dtex, more preferably 0.10 to 0.35 dtex. If the average fineness of the first fibers exceeds 0.40 dtex, the solidity of the surface layer that is adhered to the grain surface resin layer of the artificial leather substrate decreases.
[0046] Also, the average fineness of the second fibers formed from the second fiber web is 0.05~0 .60dte x The average fineness of the second fibers is preferably 0.05 to 0.55 dtex, and more preferably 0.1 to 0.40 dtex. If the average fineness of the second fibers exceeds 0.60 dtex, the texture of the resulting grain-finished artificial leather will deteriorate. In addition, it will be difficult to adjust the porosity A of the first region to 10 to 20% or less and the porosity B of the second region to 2 to 3.3 times the porosity A, as described below.
[0047] The average fiber length of the islands-in-the-sea type composite fibers for forming the first fiber web and the second fiber web is not particularly limited. In the case of long fibers (continuous fibers) obtained by continuous spinning using a spunbonding method, fibers having a fiber length of, for example, 100 mm or more, or even 200 mm or more, particularly several meters, several hundred meters, and especially several kilometers or more are obtained. In the case of fibers obtained by cutting melt-spun islands-in-the-sea type composite fibers, short fibers having a length of less than 100 mm, or even about 30 to 80 mm are produced.
[0048] The first islands-in-sea type composite fibers forming the first fiber web may be either long fibers or short fibers, but are particularly preferably long fibers because they are easily heat-shrinkable, resulting in a denser fiber structure and a lower porosity. The second islands-in-sea type composite fibers forming the second fiber web may be either long fibers or short fibers, but are particularly preferably short fibers because they are easily heat-shrinkable, resulting in a sparser fiber structure and a higher porosity.
[0049] By such a method, it is possible to produce a first fiber web containing first islands-in-sea type composite fibers for forming first fibers having an average fineness of 0.40 dtex or less, and a second fiber web containing second islands-in-sea type composite fibers for forming second fibers having an average fineness of 0.60 dtex or less.
[0050] (2) forming a laminated web by laminating at least one layer of a second fiber web onto at least one surface of at least one layer of a first fiber web; Next, the first fiber web and the second fiber web are layered on top of each other to a predetermined basis weight to form a layered web.
[0051] As a method for producing a laminated web, for example, there is cross wrapping in which about 4 to 100 sheets are stacked using a cross wrapper so that at least one layer of a second fiber web is arranged on at least one side, preferably both sides, of at least one layer of a first fiber web to obtain a desired basis weight. The number of layers of the first fiber web and the second fiber web is appropriately adjusted according to the basis weight of each fiber web. In addition, woven fabrics, knitted fabrics, other nonwoven fabrics, etc. may be stacked as necessary, as long as the effect of the present invention is not impaired.
[0052] In addition, when cross-lapping, in order to prevent the needles from breaking or being damaged during needle punching, it is preferable to apply an oil agent to prevent needle breakage or an antistatic agent to the surface of the fibers used or to the surface of the fiber web.
[0053] The ratio of the first fiber web to the second fiber web is not particularly limited, but in the grain-finished artificial leather, the thickness ratio of the first nonwoven fabric layer to the total thickness of the first nonwoven fabric layer formed from the first fiber web and the second nonwoven fabric layer formed from the second fiber web is preferably 30 to 60%, or more preferably 35 to 55%.
[0054] (3) A step of forming an entangled fiber sheet by entangling the first islands-in-sea type composite fiber with the second islands-in-sea type composite fiber. Next, the first islands-in-sea type composite fibers forming the first fiber web and the second islands-in-sea type composite fibers forming the second fiber web are entangled to form an entangled fiber sheet. The entangled fiber sheet is formed by subjecting the laminated web to an entanglement treatment using a known nonwoven fabric manufacturing method such as needle punching or high-pressure water jet treatment. In this embodiment, the entanglement treatment by needle punching will be described in detail as a representative example.
[0055] A silicone-based oil or a mineral-based oil, such as an oil for preventing needle breakage, an antistatic oil, or an oil for improving entanglement, is applied to the laminated web, and then an entanglement treatment is performed by needle punching to three-dimensionally entangle the first islands-in-sea type composite fibers and the second islands-in-sea type composite fibers.
[0056] In the needle punching process, needle punching is performed under conditions where at least one barb penetrates from one side or both sides simultaneously or alternately. The punching density depends on the basis weight and fiber density of the laminated web, but is generally 1000 to 5000 P (punches) / cm. 2 , and even 1500~4000P / cm 2 From the viewpoint of maintaining high mechanical properties, it is preferable that the above-mentioned range is satisfied.
[0057] The basis weight of the entangled fiber sheet obtained by entangling the first islands-in-sea type composite fibers and the second islands-in-sea type composite fibers forming the laminated web thus produced is not particularly limited, but is preferably 200 to 1500 g / m 2 , and even 300 to 1000 g / m 2is preferable since it is possible to obtain an artificial leather substrate having an excellent balance between mechanical properties and suitable processability.
[0058] (4) A step of forming a heat-shrinkable fiber sheet by heat-shrinking the entangled fiber sheet. Next, the entangled fiber sheet is heat-shrunk to increase the fiber density and degree of entanglement of the entangled fiber sheet. Specific examples of the heat-shrinking treatment include a method of continuously contacting the entangled fiber sheet with water vapor, and a method of adding water to the entangled fiber sheet and then heating the water with heated air or electromagnetic waves such as infrared rays. The entangled fiber sheet densified by the heat-shrinking treatment may be further heat-pressed from one or both sides to adjust the fiber density of the first nonwoven fabric layer and the second nonwoven fabric layer to be formed.
[0059] The change in basis weight of the entangled fiber sheet in the heat shrinkage treatment step is preferably at least 1.1 times (mass ratio), more preferably at least 1.3 times and no more than 2 times, even more preferably no more than 1.6 times, compared to the basis weight before the heat shrinkage treatment.
[0060] The basis weight of the heat-shrinkable fiber sheet thus produced is not particularly limited, but is preferably 350 to 2800 g / m 2 , and even 550~1800g / m 2 is preferable since it is possible to obtain an artificial leather substrate having an excellent balance between mechanical properties and suitable processability.
[0061] (5) A process of applying water-based polyurethane to the heat-shrinkable fiber sheet In the production of the artificial leather substrate, the heat-shrinkable fiber sheet obtained in step (4) is impregnated with an aqueous polyurethane in order to impart shape stability to the artificial leather substrate and to enhance the feeling of fullness. After the aqueous polyurethane is imparted to the heat-shrinkable fiber sheet obtained in step (4), the islands-in-the-sea type composite fiber is subjected to an ultrafine fiber processing in step (6), so that the first and second fibers formed are not excessively restricted by the aqueous polyurethane, and an artificial leather substrate having an excellent supple feel is obtained.
[0062] The water-based polyurethane is a polyurethane derived from an aqueous polyurethane dispersion, such as an emulsion or dispersion in which the water-based polyurethane or its prepolymer is dispersed in an aqueous medium. The water-based polyurethane is obtained, for example, by reacting urethane raw materials including a diisocyanate compound having two isocyanate groups, a polymer diol, a chain extender, and, if necessary, a polyfunctional compound or an acid group-containing compound.
[0063] The diisocyanate compound is a compound having two isocyanate groups. Specific examples thereof include aliphatic diisocyanates such as hexamethylene diisocyanate; alicyclic diisocyanates such as isophorone diisocyanate, norbornene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and 1,4-bis(isocyanatomethyl)cyclohexane; aromatic diisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), and xylylene diisocyanate; polyfunctional isocyanates and their isocyanate block compounds, which are polyfunctional compounds that give branched structures such as trifunctional and tetrafunctional isocyanates such as isocyanurate type, biuret type, and adduct type. These may be used alone or in combination of two or more types.
[0064] The polymer diol is a polymer diol having two hydroxyl groups. Specific examples thereof include polypropylene carbonate diol, poly(2-methyl-1,3-propylene carbonate) diol, polytetramethylene carbonate diol, polypentamethylene carbonate diol, polyhexamethylene carbonate diol, poly(3-methyl-1,5-pentylene carbonate) diol, polypentamethylene carbonate diol, polytetramethylene carbonate diol, polyoctamethylene carbonate diol, poly(2-methyl-1,8-octylene carbonate) diol, polynonamethylene carbonate diol, polydecamethylene polycarbonate diol, polydodecamethylene polycarbonate, Examples of the diol include polycarbonate diols such as ethyl acetate diols or copolymers thereof; polyether diols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and poly(methyltetramethylene glycol) or copolymers thereof; polyester diols such as polybutylene adipate diol, polybutylene sebacate diol, polyhexamethylene adipate diol, poly(3-methyl-1,5-pentylene adipate) diol, poly(3-methyl-1,5-pentylene sebacate) diol, and polycaprolactone diol or copolymers thereof; and polymer diols such as polyester carbonate diols. These may be used alone or in combination of two or more. Among these, it is preferable to use a polymer diol containing at least one selected from polypropylene carbonate diol, poly(2-methyl-1,3-propylene carbonate) diol, polytetramethylene carbonate diol, polypentamethylene carbonate, polyhexamethylene carbonate diol, poly(3-methyl-1,5-pentylene carbonate) diol, polypentamethylene carbonate diol, polytetramethylene carbonate diol, polyoctamethylene carbonate diol, poly(2-methyl-1,8-octylene carbonate) diol, polynonamethylene carbonate diol, polynonamethylene polycarbonate diol, and polydecamethylene polycarbonate diol.
[0065] The chain extender is a low molecular weight compound having two functional groups having active hydrogen such as a hydroxyl group or an amino group. Specific examples of the chain extender include hydrazine, ethylenediamine, propylenediamine, hexamethylenediamine, nonamethylenediamine, xylylenediamine, isophoronediamine, piperazine and derivatives thereof; diamines such as adipic acid dihydrazide and isophthalic acid dihydrazide; triamines such as diethylenetriamine; tetramines such as triethylenetetramine; diols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-bis(β-hydroxyethoxy)benzene, and 1,4-cyclohexanediol; amino alcohols such as aminoethyl alcohol and aminopropyl alcohol. These may be used alone or in combination of two or more.
[0066] Water-based polyurethane may be crosslinked to improve water resistance, abrasion resistance, and hydrolysis resistance. The crosslinking agent for crosslinking polyurethane may be an external crosslinking agent added to polyurethane as a third component, or an internal crosslinking agent that introduces reactive points that will become a crosslinked structure in advance into the polyurethane molecular structure. Examples of the crosslinking agent include compounds having an isocyanate group, an oxazoline group, a carbodiimide group, an epoxy group, a melamine resin, and a silanol group.
[0067] Examples of polyurethane aqueous dispersions include emulsions or dispersions containing self-emulsifying polyurethanes with anionic hydrophilic groups such as those with acid groups introduced into the urethane skeleton, cationic hydrophilic groups such as those with ionic groups such as ammonium groups introduced into the urethane skeleton, and nonionic hydrophilic groups introduced into the urethane skeleton; emulsions of forced emulsifying polyurethanes in which polyurethanes without hydrophilic groups are forcedly emulsified with an emulsifier; and emulsions or dispersions in which self-emulsifying polyurethanes and forced emulsifying polyurethanes are used in combination. Among these, emulsions of self-emulsifying polyurethanes with anionic hydrophilic groups such as those with acid groups introduced into the urethane skeleton, emulsions of forced emulsifying polyurethanes without hydrophilic groups, or combinations of these are preferred in terms of excellent dispersion stability.
[0068] The polyurethane aqueous dispersion may contain, as necessary, pigments such as carbon black, dyes, mildew inhibitors and antioxidants, ultraviolet absorbers, light resistance agents such as light stabilizers, flame retardants, penetrating agents and lubricants, antiblocking agents such as silica and titanium oxide, water repellents, viscosity adjusters, surfactants such as antistatic agents, antifoaming agents such as silicone, fillers such as cellulose, coagulation adjusters, and inorganic particles such as silica and titanium oxide.
[0069] The proportion of the water-based polyurethane is 5 to 18% by mass, preferably 6 to 18% by mass, and more preferably 7 to 15% by mass, based on the obtained artificial leather substrate, in order to avoid insufficient or excessive binding of the ultrafine fiber bundles. If the content of the water-based polyurethane is less than 5% by mass, the shape stability and processability are reduced. If the content of the water-based polyurethane exceeds 18% by mass, the ultrafine fiber bundles are too constrained and become hard, and the fibers forming the second nonwoven fabric layer, which has a low fiber density, are too constrained and become difficult to stretch, which makes the surface more likely to become uneven.
[0070] As a method for impregnating a heat-shrinkable fiber sheet with an aqueous polyurethane, for example, a dip-nip method is used in which a heat-shrinkable fiber sheet is immersed in a bath filled with an aqueous polyurethane dispersion, and then squeezed with a press roll or the like once or multiple times until the sheet is impregnated to a desired state.
[0071] The aqueous polyurethane dispersion is impregnated into a heat-shrinkable fiber sheet, and the aqueous polyurethane dispersion is dried and solidified, thereby impregnating the heat-shrinkable fiber sheet with the aqueous polyurethane. In order to crosslink the solidified aqueous polyurethane, a heat treatment or aging treatment may be performed after solidification and drying.
[0072] (6) A step of forming a fiber-entangled body including a first nonwoven fabric layer and a second nonwoven fabric layer by subjecting the heat-shrinkable fiber sheet to an ultrafine fiber treatment to which the water-based polyurethane has been applied. In this process, the islands-in-the-sea type composite fibers in the heat-shrinkable fiber sheet are subjected to an ultrafine fiber processing to form a fiber-entangled body including a first nonwoven fabric layer mainly made of the first fibers and a second nonwoven fabric layer mainly made of the second fibers.
[0073] A fiber-entangled body including a first nonwoven fabric layer mainly made of a first fiber and a second nonwoven fabric layer mainly made of a second fiber is formed by extracting or decomposing and removing the sea component from the islands-in-sea type composite fibers contained in a heat-shrinkable fiber sheet with water, a solvent, etc., and converting the fibers into ultrafine fibers in the form of fiber bundles. For example, in the case of islands-in-sea type composite fibers using a water-soluble polyvinyl alcohol-based resin as the sea component, the water-soluble polyvinyl alcohol-based resin, which is the sea component, is removed by hot water heating treatment with water, an alkaline aqueous solution, an acidic aqueous solution, etc.
[0074] The first fibers have an average fineness of 0.40 dtex or less, preferably 0.075 to 0.40 dtex, and more preferably 0.09 to 0.35 dtex. If the average fineness of the first fibers exceeds 0.40 dtex, the solidity of the surface layer that is applied to the grain surface resin layer of the artificial leather substrate decreases.
[0075] The second fibers have an average fineness of 0.60 dtex or less, preferably 0.05 to 0.55 dtex, more preferably 0.10 to 0.40 dtex. If the average fineness of the second fibers exceeds 0.60 dtex, the texture of the resulting grain-finished artificial leather deteriorates.
[0076] The first nonwoven fabric layer has a higher fiber density than the second nonwoven fabric layer. The fiber density is not particularly limited, but can be calculated, for example, as follows. The number of ultrafine fibers that fall within a 50 μm × 50 μm area where the fiber cross sections are aligned near the center of the thickness direction of each nonwoven fabric layer is counted. Then, the average cross-sectional area (μm 2 For example, the specific gravity of polyethylene terephthalate is 1.4 g / cm 3 Then, the fiber density is calculated by multiplying the average cross-sectional area of the microfibers by the number of microfibers.
[0077] It is preferable that the fiber density of the first nonwoven fabric layer is 1.1 to 2.5 times that of the second nonwoven fabric layer, because the difference in void ratio as described above can be created by the difference in fiber densities, thereby increasing the solidity of only the surface layer of the first nonwoven fabric layer that is attached to the silver surface resin layer, making it easier for fine creases to occur on the surface of the silver surface resin layer when folded.
[0078] As described above, such a difference in fiber density can be adjusted to the above-mentioned void ratio by making the ratio of island components of the first islands-in-sea type composite fibers for forming the first fibers higher than the ratio of island components of the second islands-in-sea type composite fibers for forming the second fibers, by making the average fineness of the first fibers lower than the average fineness of the second fibers, or by lowering the content ratio of the first fibers to the total thickness of the first fibers and the second fibers.
[0079] Specifically, the fiber density of the first nonwoven fabric layer can be made higher than the fiber density of the second nonwoven fabric layer by adjusting the island component ratio of the first islands-in-sea type composite fibers to be 10 to 30 mass % higher than the island component ratio of the second islands-in-sea type composite fibers, or by adjusting the average fineness of the second fibers to be 1.5 times or more higher than the average fineness of the first fibers.
[0080] The first and second fibers thus formed form a fiber bundle. Specifically, for example, it is preferable that 5 to 200, more preferably 10 to 50, and particularly preferably 10 to 30 ultrafine fibers are present in a fiber bundle. The first and second fibers being present as a fiber bundle exhibits higher mechanical strength.
[0081] Through the above steps, an intermediate artificial leather substrate is obtained. After drying, the intermediate artificial leather substrate is sliced into a plurality of pieces in a direction perpendicular to the thickness direction or is ground to adjust the thickness.
[0082] (7) A step of flattening the surface of the first nonwoven fabric layer to form an artificial leather substrate. Next, the surface of the first nonwoven fabric layer of the intermediate of the artificial leather substrate is flattened to form the artificial leather substrate. Specifically, the surface of the first nonwoven fabric layer of the intermediate of the artificial leather substrate is flattened by buffing the surface layer with sandpaper or the like. In addition to flattening, finishing treatments such as kneading softening treatment, reverse seal brushing treatment, antifouling treatment, hydrophilic treatment, lubricant treatment, softener treatment, antioxidant treatment, ultraviolet absorbing agent treatment, fluorescent agent treatment, and flame retardant treatment may be performed as necessary.
[0083] The basis weight of the artificial leather substrate thus formed is not particularly limited, but is, for example, 100 to 1000 g / m 2 , and even 200 to 600 g / m 2 It is preferable that:
[0084] The apparent density of the artificial leather substrate is, for example, 0.30 to 0.70 g / cm3 Furthermore, 0.50 to 0.70 g / cm 3 , especially 0.50~0.60g / cm 3 This is preferable since it is possible to obtain a grain-finished artificial leather having a superior feeling of fullness.
[0085] (8) A step of applying a grain-surface resin layer to the surface of the flattened first nonwoven fabric layer. A grain-finished artificial leather is obtained by applying a grain-finish resin layer to the surface of the first nonwoven fabric layer of the flattened artificial leather substrate. Methods for applying a grain-finish resin layer to the surface of the artificial leather substrate include, for example, a dry surfacing method in which a polymeric elastomer is coated on a release paper and then attached to the surface of the artificial leather substrate, and a direct coating method in which a resin-containing coating liquid is directly applied to the surface of the artificial leather substrate by a roll coater or spray coater, and then dried to form a layer. Among these, the dry surfacing method is preferred because it is easy to adjust the thickness of the grain-finish resin layer and has excellent processability.
[0086] The dry surface forming method is a method in which a coating liquid containing a resin for forming a colored resin layer for forming a grain surface layer is applied onto a release sheet as a grain surface resin layer, the resin layer is then dried to form a resin layer, the resin layer is attached to the surface of an artificial leather substrate via an adhesive layer constituting the grain surface resin layer, and the release sheet is then peeled off. The grain surface resin layer may also be formed with an uneven pattern such as a grain pattern by embossing or the like. Examples of embossing include a method in which a grain surface layer film is formed on a grained release paper having a grain pattern applied to its surface, or a method in which a grain pattern is transferred to the grain surface resin layer while the grain surface resin layer is still uncured, and then the grain surface resin layer is cured.
[0087] As the resin component for forming the silver surface resin layer, a polymeric elastomer such as polyurethane, acrylic elastomer, silicone elastomer, diene elastomer, nitrile elastomer, fluorine-based elastomer, polystyrene elastomer, polyolefin elastomer, polyamide elastomer, or halogen-based elastomer is preferably used.
[0088] The thickness of the silver surface resin layer is not particularly limited, but is preferably 30 to 500 μm, more preferably 40 to 100 μm. The thickness of the adhesive layer constituting the silver surface resin layer is preferably 10 to 300 μm, more preferably 30 to 100 μm.
[0089] In this manner, an artificial leather substrate is obtained, which includes a fiber-entangled body including a first nonwoven fabric layer mainly made of a first fiber and a second nonwoven fabric layer mainly made of a second fiber, and 5 to 18 mass % of a water-based polyurethane provided in the voids in the fiber-entangled body, and a grain-finished artificial leather coated on one side of the first nonwoven fabric layer.
[0090] 1, the grain-finished artificial leather thus obtained is adjusted so that in a first region R1, which is a 200 μm-thick region extending from the interface between the grain surface resin layer 4 and the first nonwoven fabric layer 1 toward the second nonwoven fabric layer, and a second region R2, which is a region excluding the first region R1, the porosity A of the first region R1 is 10 to 20%, and the porosity B of the second region R2 is 2 to 3.3 times the porosity A. Preferably, the porosity B of the second region R2 is 15 to 40%, or even 16 to 35%, higher than the porosity A of the first region R1, from the viewpoint of sufficiently obtaining the effect of preventing fine creases from occurring on the surface and surface defects from occurring.
[0091] The grain-finished artificial leather of this embodiment is adjusted to the above-mentioned void ratio relationship by making the fiber density of the first nonwoven fabric layer higher than that of the second nonwoven fabric layer. By adjusting in this way, grain-finished artificial leather is obtained that can maintain a supple texture while making the surface wrinkles fine and further suppressing the occurrence of surface defects during stitching. Such grain-finished artificial leather is preferably used for various applications that require a luxurious feel, such as shoes, bags, interior decorations, wall decorations, and miscellaneous goods. EXAMPLES
[0092] The present invention will be described in more detail below with reference to examples, although the scope of the present invention is not limited to these examples.
[0093] First, the evaluation methods used in the present examples will be summarized below.
[0094] Average fineness The average fineness was calculated by taking a scanning electron microscope (SEM) photograph of the cross section of the grain-finished artificial leather at 3,000x magnification, randomly selecting 10 fiber cross sections, measuring the cross-sectional area, calculating the average cross-sectional area, and converting it into the density of each resin.
[0095] <Apparent density of artificial leather substrate and heat shrinkable fiber sheet> According to JIS L1913, thickness (mm) and basis weight (g / m 2 ) and calculate the apparent density (g / cm 3 ) was calculated.
[0096] <Porosity measurement> The cross section of the entire layer of the grain-finished artificial leather was observed with a scanning electron microscope at a magnification of 70 times. The obtained photograph was divided into an image of a first region up to 200 μm from the interface between the grain surface resin layer 4 and the first nonwoven fabric layer 1 and an image of a second region below the first region using image analysis software PopImaging (manufactured by Digitalbeing kids.Co). Then, using the binarization tool of image pro premier (media cybernetics), binarization processing was performed with a threshold value of 150, voids were judged to be black and others to be white, the number of black dots and the number of white dots in the histogram tool were read, and the porosity A of the first region and the porosity B of the second region were calculated by the formula of black dot number / (white dot number+black dot number)×100(%).
[0097] <Evaluation of creases> A square test piece measuring 6 cm in length and 6 cm in width was cut out from the grain-finished artificial leather. The test piece was then folded with the grain side of the resin layer inward and placed between the jaws of a caliper spaced 1 cm apart, and any creases that occurred at the fold were observed. The grade of creases was determined according to the STD174 Break / Pipiness Scale (manufactured by SATRA, UK) which has a rating of grades from 1 to 8. Grade 1 indicates the finest creases and grade 8 indicates the coarsest creases.
[0098] <Face-to-face evaluation> A test piece was prepared by cutting the grain-finished artificial leather into a diameter of 9 cm. Then, in accordance with the hemispherical plasticity test method for leather specified in JIS K6546, pressure was applied to the side of the test piece where the grain resin layer was not formed, and the test piece was stretched until the line drawn on the surface of the grain resin layer was stretched by 20%, and the surface condition in that state was judged according to the following criteria. Grade 1: No unevenness at all Grade 2: Almost no unevenness Grade 3: Slightly uneven Grade 4: Many bumps and grooves
[0099] <Texture evaluation> The obtained grain-finished artificial leather was bent, and the feel of stiffness and flexibility was judged according to the following criteria. A: It had a rich feel, was not easily broken, and had excellent flexibility. B: The texture was one or more of the following: lacking in solidity, prone to breaking, and hard.
[0100] <Proportion of the first nonwoven fabric layer> The cross section of the grain-finished artificial leather in the thickness direction of all layers was observed with a scanning electron microscope at a magnification of 70 times, and a cross section photograph was taken. From the cross section photograph obtained, the distance X from the interface between the first nonwoven fabric layer and the grain surface resin layer to the lower surface of the grain-finished artificial leather, and the distance Y from the interface between the first nonwoven fabric layer and the grain surface resin layer to the interface between the first nonwoven fabric layer and the second nonwoven fabric layer were measured. The proportion (%) of the first nonwoven fabric layer was calculated from Y / X×100. X and Y were measured at three arbitrarily selected points, and the proportion of the first nonwoven fabric layer at the three points was calculated, and the average value was obtained.
[0101] <Fiber density> The cross section of the entire layer of the grain-finished artificial leather in the thickness direction was observed with a scanning electron microscope at a magnification of 400 times, and a cross-sectional photograph was taken. From the cross-sectional photograph obtained, the number N1 of ultrafine fibers falling within a 50 μm × 50 μm area where the fiber cross sections are aligned near the center of the thickness direction of the first nonwoven fabric layer was counted. Then, from the average fineness measured in advance, the average cross-sectional area S1 (μm 2 The specific gravity of the ultrafine fibers was calculated based on the specific gravity of polyethylene terephthalate, which is 1.4 g / cm. 3 The fiber density of the first nonwoven fabric layer was calculated by multiplying the average cross-sectional area S1 of the ultrafine fibers by the number N1 of the ultrafine fibers, N1×S1. The fiber density of the second nonwoven fabric layer was calculated by multiplying the number N2 of the ultrafine fibers by the average cross-sectional area S2 of the ultrafine fibers, N2×S2, in the same manner as the first nonwoven fabric layer. Note that N1×S1 and N2×S2 are the total cross-sectional areas of the ultrafine fibers in a range of 50 μm×50 μm, and the larger the area, the higher the fiber density. The fiber density was calculated at three arbitrarily selected points, and the average value was calculated.
[0102] [Example 1] A water-soluble thermoplastic polyvinyl alcohol resin (PVA; sea component) and an isophthalic acid-modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt composite spinning die (number of islands: 25 islands / fiber) at 260°C so that the sea component / island component ratio was 25 / 75 (mass ratio), and the ejector pressure was adjusted so that the spinning speed was 3700 m / min, and the long fibers were collected on a net. In this way, a first fiber web A1 containing first islands-in-sea type composite fibers with an average fineness of 3.0 dtex was obtained.
[0103] On the other hand, PVA and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt conjugate spinning die (number of islands: 12 islands / fiber) at 260°C so that the sea component / island component ratio was 50 / 50 (mass ratio), and spun at a spinning speed of 800 m / min. Next, the fibers were drawn to spin a second islands-in-sea type conjugate fiber with an average fineness of 7.5 dtex, and then crimped. The obtained crimped second islands-in-sea type conjugate fiber was cut to 51 mm and passed through a carding machine to obtain a second fiber web B1.
[0104] Next, the obtained web was laminated with a mass ratio of the second fiber web B1 / the first fiber web A1 / the second fiber web B1=1 / 1.2 / 1 to form a laminated web. Then, the laminated web was subjected to a 3450 P / cm 2 test using 1-barb and 6-barb needles. 2 By needle punching at a punching density of 730g / m 2 An entangled fiber sheet was formed.
[0105] Next, the entangled fiber sheet was subjected to steam treatment under conditions of 110°C and 23.5% RH. Then, it was dried in an oven at 90 to 110°C, and further, it was heat pressed at 120°C to obtain a basis weight of 1158 g / m 2 , apparent density 0.60g / cm 3 Thus, a heat-shrinkable fiber sheet having a thickness of 2.1 mm was obtained.
[0106] Next, the heat-shrinkable fiber sheet was impregnated with an aqueous polyurethane emulsion (solid content 14.5% by mass) at a pick-up rate of 45%. The aqueous polyurethane was a polycarbonate-based non-yellowing polyurethane. Furthermore, 1.5 parts by mass of a carbodiimide-based crosslinking agent and 8.3 parts by mass of ammonium sulfate were added to the emulsion per 100 parts by mass of polyurethane, and the polyurethane solid content was adjusted to 10% by mass. The heat-shrinkable fiber sheet impregnated with the emulsion was then dried at 115°C under a 25% RH atmosphere, and further dried at 150°C.
[0107] The heat-shrinkable fiber sheet to which the polyurethane had been applied was then immersed in hot water at 95°C for 10 minutes while being subjected to nip treatment and high-pressure water jet treatment to dissolve and remove the PVA. In this manner, a fiber-entangled body was formed including a first nonwoven fabric layer mainly made of a first fiber layer having an average fineness of 0.1 dtex and a second nonwoven fabric layer mainly made of a second fiber having an average fineness of 0.3 dtex on both sides of the first nonwoven fabric layer. The intermediate product of the artificial leather substrate was then obtained by drying.
[0108] The intermediate artificial leather substrate was then sliced in half at the center. The sliced surface was designated the main surface, and the opposite surface was designated the back surface. The sliced back surface of the intermediate artificial leather substrate was then treated with #600 paper to remove fuzz that is prone to falling off, and the surface was ground with #600 paper to make it flat. In this way, a 346 g / m2 substrate was obtained. 2 , apparent density 0.53g / cm 3 Thus, an artificial leather substrate having a thickness of 0.65 mm was produced.
[0109] Then, the surface of the release paper was coated with a polyurethane solution for the surface layer and dried to form a surface layer with a thickness of 25 μm, and further, the surface layer was coated with a polyurethane solution for the intermediate layer and dried to form an intermediate layer with a thickness of 30 μm, and further, the intermediate layer was coated with a polyurethane solution for the adhesive layer and dried to form an adhesive layer with a thickness of 60 μm. Then, a grain surface resin layer including the surface layer, intermediate layer, and adhesive layer formed on the release paper was dry laminated via the adhesive layer on the main surface of the artificial leather substrate to perform a dry surface treatment. Then, the product was dried at 100° C. for 2 minutes, and further aged at 60° C. for 2 days, and then the release paper was peeled off to obtain a grain-finished artificial leather. Then, the product was evaluated by the above-mentioned evaluation method. FIG. 1 shows a scanning electron microscope (SEM) photograph of a cross section in the thickness direction of the grain-finished artificial leather obtained in Example 1.
[0110] The results are shown in Table 1 below.
[0111] [Table 1]
[0112] [Example 2] In Example 1, the second fiber web B1 / the first fiber web A1 / the second fiber web B1 were laminated at a mass ratio of 1 / 1.1 / 1 instead of 1 / 1.2 / 1. In addition, by changing the clearance of the heat press roll, the apparent density was increased to 0.65 g / cm. 3 A heat-shrinkable fiber sheet of the above composition was prepared. A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except for the above. The results are shown in Table 1.
[0113] [Example 3] In Example 1, the second fiber web B1 / the first fiber web A1 / the second fiber web B1 were laminated at a mass ratio of 1 / 1.1 / 1 instead of 1 / 1.2 / 1. In addition, by changing the clearance of the heat press roll, the apparent density was increased to 0.70 g / cm. 3 A heat-shrinkable fiber sheet of the above composition was prepared. A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except for the above. The results are shown in Table 1.
[0114] [Example 4] PVA (sea component) and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt conjugate spinning die (number of islands: 12 islands / fiber) at 260°C so that the sea component / island component ratio was 50 / 50 (mass ratio), and the ejector pressure was adjusted so that the spinning speed was 3700 m / min. The long fibers were collected on a net to obtain a second fiber web B2 containing islands-in-sea type conjugate fibers with an average fineness of 4.3 dtex. A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that the obtained second fiber web B2 was used instead of the second fiber web B1. The results are shown in Table 1.
[0115] [Example 5] PVA (sea component) and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt composite spinning die (number of islands: 12 islands / fiber) at 260°C so that the sea component / island component ratio was 25 / 75 (mass ratio), and the ejector pressure was adjusted so that the spinning speed was 3700 m / min. The long fibers were collected on a net to obtain a first fiber web A2 containing islands-in-sea composite fibers with an average fineness of 3.0 dtex. A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that the first fiber web A2 obtained was used instead of the first fiber web A1. The results are shown in Table 1.
[0116] [Example 6] A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that the impregnation conditions for the aqueous polyurethane were changed so that the content of the aqueous polyurethane was adjusted to 5% by mass instead of 10% by mass. The results are shown in Table 1.
[0117] [Example 7] A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that the impregnation conditions for the aqueous polyurethane were changed so that the content of the aqueous polyurethane was adjusted to 15% by mass instead of 10% by mass. The results are shown in Table 1.
[0118] [Example 8] PVA (sea component) and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt composite spinning nozzle (number of islands: 12 islands / fiber) at 260°C so that the sea component / island component ratio was 25 / 75 (mass ratio). The ejector pressure was adjusted so that the spinning speed was 3700 m / min. The long fibers were collected on a net to obtain a first fiber web A3 containing islands-in-sea type composite fibers with an average fineness of 4.5 dtex. Also, PVA and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt composite spinning die (number of islands: 6 islands / fiber) at 260°C so that the sea component / island component ratio was 50 / 50 (mass ratio), and spun at a spinning speed of 800 m / min. Next, the fibers were drawn to obtain fibers with an average fineness of 5.0 dtex, and then crimped. The obtained crimped fibers were cut to 51 mm and passed through a carding machine to obtain a second fiber web B3. Then, a grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that the first fiber web A3 was used instead of the first fiber web A1, and the second fiber web B3 was used instead of the second fiber web B1. The results are shown in Table 1.
[0119] [Comparative Example 1] A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that in the dry surfacing treatment of Example 1, instead of dry laminating the grain-finished resin layer to the main surface of the artificial leather substrate via an adhesive layer, the grain-finished resin layer was dry laminated to the back surface. The results are shown in Table 1. Also, Fig. 2 shows an SEM photograph of a cross section in the thickness direction of the grain-finished artificial leather obtained in Comparative Example 1.
[0120] [Comparative Example 2] A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 2, except that in the dry surface treatment in Example 2, instead of dry laminating the grain surface resin layer to the front side of the artificial leather substrate via an adhesive layer, the grain surface resin layer was dry laminated to the back side. The results are shown in Table 1.
[0121] [Comparative Example 3] A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 3, except that in the dry surface treatment of Example 3, instead of dry laminating the grain surface resin layer to the front side of the artificial leather substrate via an adhesive layer, the grain surface resin layer was dry laminated to the back side. The results are shown in Table 1.
[0122] [Comparative Example 4] PVA (sea component) and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt conjugate spinning die (number of islands: 12 islands / fiber) at 260°C so that the sea component / island component ratio was 60 / 40 (mass ratio), spun at a spinning speed of 800 m / min, and drawn to spin a second islands-in-sea type conjugate fiber with an average fineness of 8.1 dtex, and further crimped the second islands-in-sea type conjugate fiber. The obtained crimped second islands-in-sea type conjugate fiber was cut to 51 mm and passed through a carding machine to obtain a second fiber web B4.
[0123] The second fiber web in Example 5 was B4, and the second fiber web B4 was laminated in a mass ratio of 1 / 3.2 / 1. The entangled fiber sheet was subjected to steam treatment under conditions of 110°C and 23.5% RH, dried in an oven at 90 to 110°C, and then heat pressed at 120°C with the clearance of the heat press roll changed, resulting in an apparent density of 0.70 g / cm. 3 A heat-shrinkable fiber sheet having the above composition was obtained. The solid content of the polyurethane was adjusted to 8% by mass. Except for this, a grain-finished artificial leather was obtained and evaluated in the same manner as in Example 5. The results are shown in Table 1.
[0124] [Comparative Example 5] PVA (sea component) and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol% were extruded from a melt conjugate spinning die (number of islands: 12 islands / fiber) at 260°C so that the sea component / island component ratio was 50 / 50 (mass ratio), spun at a spinning speed of 800 m / min, and drawn to spin a second islands-in-sea type conjugate fiber with an average fineness of 8.1 dtex. Furthermore, the second islands-in-sea type conjugate fiber was crimped. The obtained crimped second islands-in-sea type conjugate fiber was cut to 51 mm and passed through a carding machine to obtain a second fiber web B5.
[0125] In Example 5, B5 was used as the second fiber web, and the second fiber web B5 was laminated in a mass ratio of 1 / 3.2 / 1. The entangled fiber sheet was subjected to steam treatment under conditions of 110°C and 23.5% RH, dried in an oven at 90 to 110°C, and then heat pressed at 120°C with the clearance of the heat press roll changed, resulting in an apparent density of 0.70 g / cm. 3 A heat-shrinkable fiber sheet having the above composition was obtained. The solid content of the polyurethane was adjusted to 8% by mass. Except for this, a grain-finished artificial leather was obtained and evaluated in the same manner as in Example 5. The results are shown in Table 1.
[0126] [Comparative Example 6] A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that only the first fiber web A1 was used instead of laminating the second fiber web B1 / the first fiber web A1 / the second fiber web B1 in a mass ratio of 1 / 1.2 / 1 in Example 1. The results are shown in Table 1.
[0127] [Comparative Example 7] A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1, except that the impregnation conditions for the aqueous polyurethane were changed so that the content of the aqueous polyurethane was adjusted to 20% by mass instead of 10% by mass. The results are shown in Table 1.
[0128] [Comparative Example 8] In Example 1, the apparent density was increased to 0.55 g / cm by changing the clearance of the heat press roll. 3 A heat-shrinkable fiber sheet of the above formula was obtained. A grain-finished artificial leather was obtained and evaluated in the same manner as in Example 1 except for the above. The results are shown in Table 1.
[0129] Referring to Table 1, all of the grain-finished artificial leathers obtained in Examples 1 to 8 had small fold creases, were less susceptible to surface roughness, and had an excellent feel. On the other hand, the grain-finished artificial leathers obtained in Comparative Examples 1 to 5, in which the porosity A of the first region was high and the porosity B of the second region was less than twice the porosity A, had rough creases and noticeable surface irregularities because the surface on which the grain-surface resin layer was formed was sparse. The grain-finished artificial leather of Comparative Example 6, which includes a nonwoven fabric formed using only one type of the first fiber web A1 used to form the first nonwoven fabric layer of the grain-finished artificial leather of Example 1, also had rough creases and noticeable surface irregularities. The grain-finished artificial leather obtained in Comparative Example 7, in which the proportion of aqueous polyurethane given to the voids in the nonwoven fabric layer was too high, had excellent surface fullness and fine creases, which was preferable, but the fibers forming the nonwoven fabric layer were too constrained, and surface irregularities were noticeable when the leather was pulled in. In addition, in the case of the grain-finish artificial leather obtained in Comparative Example 8 in which the porosity B of the second region was too high, i.e., the porosity B of the second region was higher than the porosity A, the second region was too sparse and the surface fraying was noticeable when the leather was pulled in. [Explanation of symbols]
[0130] 1 First nonwoven layer 2 Second nonwoven layer 3 Artificial leather base material 4 Silver surface resin layer 5. Water-based polyurethane R1 First Region R2 Second Region 10 Silver-tone artificial leather
Claims
1. The artificial leather substrate includes a fiber-entangled body including a first nonwoven fabric layer containing 60% by mass or more of a first fiber and a second nonwoven fabric layer containing 60% by mass or more of a second fiber, and 5 to 18% by mass of a water-based polyurethane provided in voids in the fiber-entangled body, and a grain surface resin layer applied to a surface of the first nonwoven fabric layer, the first fibers have an average fineness of 0.075 to 0.40 dtex, the second fibers have an average fineness of 0.05 to 0.60 dtex, and the second fibers have an average fineness that is 1.5 times or more the average fineness of the first fibers; the first nonwoven fabric layer has a higher fiber density than the second nonwoven fabric layer; In a cross section in the thickness direction of the artificial leather substrate, In a first region, which is a region having a thickness of 200 μm extending from the interface between the silver surface resin layer and the first nonwoven fabric layer toward the second nonwoven fabric layer, and in a second region, which is a region excluding the first region, The grain-finished artificial leather is characterized in that the porosity A of the first region is 10 to 20%, and the porosity B of the second region is 2 to 3.3 times the porosity A.
2. 2. The grain-finished artificial leather according to claim 1, wherein the porosity B is 15 to 40% higher than the porosity A.
3. 3. The grain-finished artificial leather according to claim 1, wherein the fiber density of the first nonwoven fabric layer is 1.1 to 2.5 times the fiber density of the second nonwoven fabric layer.
4. 4. The grain-finished artificial leather according to claim 1, wherein the first fibers are long fibers and the second fibers are short fibers.
5. 5. The grain-finished artificial leather according to claim 1, wherein a ratio of the first nonwoven fabric layer to a total thickness of the first nonwoven fabric layer and the second nonwoven fabric layer is 30 to 60%.
6. The artificial leather substrate has a surface roughness of 0.50 to 0.70 g / cm 3 The grain-finished artificial leather according to any one of claims 1 to 5, having an apparent density of
7. 7. The grain-finished artificial leather according to claim 1, wherein the first fibers and the second fibers are polyester fibers.
8. A method for producing the grain-finished artificial leather according to any one of claims 1 to 7, preparing a first fiber web, which is a web of a first islands-in-the-sea type composite fiber for forming the first fibers, and a second fiber web, which is a web of a second islands-in-the-sea type composite fiber for forming the second fibers; laminating at least one layer of a second fibrous web on at least one surface of the at least one layer of the first fibrous web to form a laminated web; a step of forming an entangled fiber sheet by entangling the first islands-in-sea type composite fibers and the second islands-in-sea type composite fibers that form the laminated web; forming a heat-shrinkable fiber sheet by heat-shrinking the entangled fiber sheet; a step of impregnating the voids in the heat-shrinkable fiber sheet with an aqueous liquid of water-based polyurethane, and then heating and drying the sheet to impart water-based polyurethane; a step of forming a fiber-entangled body including the first nonwoven fabric layer and the second nonwoven fabric layer by subjecting the heat-shrinkable fiber sheet to an ultrafine fiber treatment to which the aqueous polyurethane has been applied; A step of flattening the surface of the first nonwoven fabric layer to form an artificial leather substrate; and applying the grain surface resin layer to the flattened surface of the first nonwoven fabric layer. a ratio of island parts of the first islands-in-sea type composite fibers being higher than a ratio of island parts of the second islands-in-sea type composite fibers.
Citation Information
Patent Citations
Leather-like sheet
JP1994280145A
Artificial leather substrate
JP1999269774A
Leather-like sheet
JP2003013369A
Artificial leather substrate
JP2005097763A
Grained artificial leather
JP2012017541A